Optimalisasi Kompetensi Prefesional Guru untuk Mengembangkan Materi Pelajaran IPS Berbasis Karakter Banyumasan di SD/MI - Amalia, Rina Rizki; Ningsih, Tutuk (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The aim of this research is to describe and analyze the optimization of teacher professional competence to develop Banyumasan character-based social studies subject matter in SD/MI. This research uses a qualitative approach with the type of library research. Data was collected using documentation techniques. The data that has been collected is then presented and analyzed using content analysis data analysis techniques. The research results show that optimizing teacher professional competence to develop Banyumasan character-based social studies subject matter can be done through the 4D strategy, namely Define, Design, Develop and Disseminate. At the definition stage, the conditions needed to develop Banyumasan character-based social studies subject matter are determined and defined. At the design stage, the teacher designs Banyumasan character-based social studies learning materials based on predetermined social studies learning indicators. At the development stage, the teacher produces social studies subject matter based on Banyumasan characters that is valid, practical and effective. At the dissemination stage, the teacher delivers social studies lesson material based on Banyumasan characters that have been developed in social studies lessons in a class. This research is the result of conceptual thinking so it must be followed up by conducting experiments. This is a limitation in this research.